Use of the standard correlation and deflection coefficient in the selection of portfolios of financial assets of variable income - Gomero Gonzáles, Nicko Alberto (2018)
A common feature of the markets where financial assets are traded in equity and fixed, is its volatility. This scenario of uncertainty generates opportunities to accumulate wealth by structuring optimal portfolios, but for that it is necessary for the investor to manage a series of financial, economic, and mathematical tools, among others, to opt for the best position in this market. Therefore, to validate portfolio selection models, descriptive statistics were used, whose monitoring operation was developed with high and low risk portfolios. The method used for the development of this work was descriptive, using historical information of different actions listed in different stock indices. In the work it is possible to demonstrate that through the use of tools it is possible to structure portfolios with different degrees of risk, which is measured by the standard deviation, in addition to determine how the stock reacts to changes in the stock market, determined with this Beta of the assets.